Journal of Applied Informatics and Technology (Editorial Note) - Journal of Applied Informatics and Technology (Journal of Applied Informatics and Technology, 2025)
The Journal of Applied Informatics and Technology (JIT) has published Volume 8, Number 1 (2026): January-June, comprising a total of 13 research articles. Each article has undergone peer review by at least three experts from different institutions. The authors revised their articles based on the reviewers’ comments until they were approved for publication. The editorial team also verified the accuracy of the content, references, and language usage to ensure the highest quality. We sincerely thank all the reviewers for their valuable feedback and thoughtful recommendations.